Association between Ghrelin Gene Variations, Body Mass Index, and Waist-to-hip Ratio in Patients with Polycystic Ovary Syndrome - Xu, L.; Shi, Y.; Gu, J.; Wang, Y.; Wang, L.; You, L.; Qi, X.; Ye, Y.; Chen, Z. (Experimental and Clinical Endocrinology & Diabetes, 2014)
To investigate the association between 2 single nucleotide polymorphisms (SNP501A/C and 604 G/A) in the promoter of the ghrelin gene and the hormonal and metabolic phenotypes of polycystic ovary syndrome (PCOS) in a Chinese population.285 patients with PCOS and 260 healthy controls were selected for a prospective, case-control study at Shandong Provincial Hospital, Jinan, China. All subjects underwent genotype analysis of the 2 single nucleotide polymorphisms of the ghrelin gene. Measurements were also taken of blood lipids, glucose, and hormone levels, and calculations of body mass index (BMI) and waist-to-hip ratio (WHR) were performed to detect hormonal and metabolic phenotypes.No significant differences in polymorphism genotypes were found between PCOS patients and healthy controls. However, the frequency of the -501 A/C A allele was significantly higher in the PCOS group than in the control group. PCOS -501 A/C A carriers had significantly higher BMI and WHR than PCOS women with the CC genotype. -604 G/A polymorphisms were not associated with clinical or biochemical characteristics of PCOS.The -501 A/C polymorphism of the ghrelin gene is associated with metabolic features of PCOS in a Chinese population.
Keywords: gene; ghrelin; polycystic ovary syndrome; single nucleotide polymorphisms